Real-time observation of organic cation reorientation in methylammonium lead iodide perovskites - Bakulin, Artem; Selig, Oleg; Bakker, Huib J.; Rezus, Yves L.A.; Müller, Christian; Glaser, Tobias; Lovrinčić, Robert; Sun, Zhenhua; Chen, Zhuoying; Walsh, Aron; Frost, Jarvist M.; Jansen, Thomas L. C. (The journal of physical chemistry letters, 2015)
The introduction of a mobile and polarized organic moiety as a cation in 3D lead-iodide perovskites brings fascinating optoelectronic properties to these materials. The extent and the time scales of the orientational mobility of the organic cation and the molecular mechanism behind its motion remain unclear, with different experimental and computational approaches providing very different qualitative and quantitative description of the molecular dynamics. Here we use ultrafast 2D vibrational spectroscopy of methylammonium (MA) lead iodide to directly resolve the rotation of the organic cations within the MAPbI3 lattice. Our results reveal two characteristic time constants of motion. Using ab initio molecular dynamics simulations, we identify these as a fast (∼300 fs) “wobbling-in-a-cone” motion around the crystal axis and a relatively slow (∼3 ps) jump-like reorientation of the molecular dipole with respect to the iodide lattice. The observed dynamics are essential for understanding the electronic properties of perovskite materials.
Gesehen am 29.07.2020